The impact of insufficient resources on the quality-of-service delivery at a primary healthcare clinic in Limpopo - Dikeledi N. Malematja; Elizabeth M. Nkosi; Sanele E. Nene (Curationis)
Background: Insufficient resources at healthcare clinics pose a serious problem, undermining the quality-of-service delivery and negatively affecting the patients as recipients of care and the staff as providers of care. The shortages often result in extended waiting periods, delayed implementation of nursing interventions, prolonged hospitalisation and the potential of increased nosocomial infections.